Pengaruh Transfer Pricing, Beban Pajak Tangguhan, Leverage dan Komite Audit terhadap Penghindaran Pajak pada Perusahaan Perbankan Periode 2022–2024 - Febriyanti Aziza; Einde Evana (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study examines the influence of governance mechanisms and financial factors on tax avoidance in banking companies listed on the Indonesia Stock Exchange during the 2022–2024 period. The research utilizes secondary data obtained from published annual reports and audited financial statements. Tax avoidance is measured using the Cash Effective Tax Rate (CETR), while the independent variables consist of transfer pricing, deferred tax expense, leverage, and the audit committee. Multiple linear regression analysis is employed to analyze the relationships between variables. The findings indicate that transfer pricing has a negative effect on tax avoidance, suggesting that banks tend to prioritize operational efficiency and adherence to tax regulations rather than aggressive tax strategies. Deferred tax expense does not show a significant impact, as it mainly reflects temporary timing differences. Leverage is found to significantly influence tax avoidance through the utilization of interest expenses. Additionally, the audit committee negatively affects tax avoidance, highlighting the role of effective oversight, strong internal controls, and sound corporate governance in reducing opportunistic tax behavior.